Uji Efektivitas Mukolitik Ramuan Buah Adas (Foeniculum vulgare Mill.) Secara In Vitro pada Putih Telur Bebek: Mucolytic Effectiveness Test of Fennel Fruit Concoction (Foeniculum vulgare Mill.) in Vitro on Duck Egg White - Desy Aryanti Pardilla Vitri; Rismiyati Rismiyati; Julia Eka Putri Ananda; Muhammad Syach; Nindia Oktaviani Adira; Siti Rahmatul Aini (JURNAL FARMASI DAN MAKANAN, 2023)
Fennel (Foeniculum vulgare) empirically has been widely used by the community as a cough medicine with added honey. This study aims to determine the mucolytic activity of fennel herb in vitro on duck egg white with a concentration of 10% and 20%. A Fennel fruit concoction is obtained by brewing it with hot water and adding a teaspoon of honey. Concoctions of 10% and 20% fennel fruit were added with tween 80 and a mixture of duck egg white and phosphate buffer solution pH 7. Ambroxol HCl 3% was used as a positive control while mucus without boiling fennel was used as a negative control. The sample was tested using an Ostwald viscometer and its density was measured with a pycnometer. The data obtained is then processed to obtain the viscosity value. The results were analyzed by a one-way ANOVA statistical test and continued with the LSD test. The result showed that there was a significant difference between the negative control and the positive control, with concentrations of 10% and 20% (p < 0.05) and there was no significant difference between the positive controls with concentrations of 10% and 20% (p > 0.05). From this study, it can be concluded that the decoction of fennel fruit with added honey is proven to have mucolytic activity at concentrations of 10% and 20%.